INDEPENDENT CAMPUS IMPLEMENTATION AT UPN “VETERAN” YOGYAKARTA - Kusumo, Yudhy Widya; Ardhanariswari, Kartika Ayu; Perdana, Arika Bagus; Indah, Sika Nur (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2020)
Independent campus policy was a form of Student Centred Learning (SCL) actual implementation. Through this policy, learning might be performed outside campus area, yet still within lecturer’s supervision. The policy implementation needed carefulness. Objective of this research was to establish the implementation of independent campus at UPN “Veteran” Yogyakarta. This research used qualitative descriptive method using in-depth interview. This research, also, used diffusion of innovation theory to see how the adaptation process performed by academics of UPN “Veteran” Yogyakarta in implementing independent campus policy. Result of this research showed that University of National Development (UPN) “Veteran” Yogyakarta satisfied Independent Campus program preparation in the future and would be elaborated and referred to 5 decision making processes. Stages in diffusion of innovation were stages of knowledge, persuasion, decision, implementation, and confirmation. Lecturer as educator had been socialized about Freedom to Learn – Independent Campus (MBKM) program. Therefore, after draft of Independent Campus had been implemented, freshmen would be the first batch that would be tried with this policy. In competency, UPN “Veteran” Yogyakarta lecturers had been known that they met the teaching quality standard. In addition, learning process method would be made creatively and innovatively to balance the MBKM dynamics.